Study of a charge transition-driven resistive switching mechanism in TiO2-based random access memory via density functional theory - Jeong, Taeyoung; Yeu, In Won; Ye, Kun Hee; Yoon, Seungjae; Kim, Dohyun; Hwang, Cheol Seong; Choi, Jung-Hae (Royal Society of Chemistry, 2024)
The nature of the conducting filament (CF) with a high concentration of oxygen vacancies (V(O)s) in oxide thin film-based resistive random access memory (RRAM) remains unclear. The V(O)s in the CF have been assumed to be positively charged (V-O(2+)) to explain the field-driven switching of RRAM, but V-O(2+) clusters in high concentration encounter Coulomb repulsion, rendering the CF unstable. Therefore, this study examined the oxidation state of V(O)s in the CF and their effects on the switching behavior via density functional theory calculations using a Pt/TiO2/Ti model system. It was concluded that the V(O)s in the CF are in a low oxidation state but are transformed to V-O(2+) immediately after release from the CF. In addition, the short-range interactions between V(O)s were confirmed to facilitate the rupture and rejuvenation of the CF by reducing the required activation energy. Finally, an improved switching model was proposed by considering the charge transition of V(O)s, providing a plausible explanation for the reported coexistence of two opposite bipolar switching polarities: the eight-wise and the counter-eight-wise polarities.